Flexible facial morphing. (2015) - Kao, Yang-Ta; Yang, Fu-Wen; Lin, Hwei Jen
In the paper, we propose a facial morphing system that uses the triangulation algorithm and linear interpolation associated with a set of indicated control points to introduce a sequence of intermediate images between the source image and the target image. The proposed system provides a guidance mode for the users so that they can follow the online instruction to mark each of the control points. With those control points the system can automatically perform triangulation algorithm and produce the intermediate images for morphing. The experimental results show that the proposed system is flexible to use and provides quite natural morphing results. In addition, the system has no limit to the shape, size, and plane rotation of the faces in both the source image and the target image.